Female and Male Activism for Women’s Rights in Eighteenth-Century America and France - Linda Garbaye (XVII-XVIII, 2015)
This paper retraces the involvement of American and French women and men in favor of women’s rights during the periods of the American War of Independence and the French Revolution. In both the United States and France, women participated in these major historical events through street protests, in their writings and correspondence, and, in rare cases, they took part in fighting. In spite of this, the issue of women’s rights remained controversial, mainly because their social role was strictly confined to domestic tasks. Nevertheless, some women and men, on both sides of the Atlantic, chose to be involved in activities favoring women’s rights. These individuals and/or groups were more or less well-known, and they came from various social backgrounds. In this article, I seek to present them, as well as the objectives and arguments they used to achieve their goal. While taking stock of the social, political and institutional specificities of each country, I will highlight the parallels between the activities of these women’s rights supporters on both sides of the Atlantic, focusing in particular on their use of the Enlightenment’s concept of natural rights and of other revolutionary ideas.